A Study on the Roads Flatness Using International Roughness Index in New Taipei City. Issue 1 (1st January 2022) - Lin, Chun; Loong Chen, Shong; Tang, Chaowei; Ang Hsieh, Hsin
Abstract: The quality of roads is an indicator of urban progress. The development of tourism and economy contributes to the increasing demands for transportation and, thus, aggravated burdens and vulnerability to damage of these roads, and the result is compromised transportation quality and safety. The Road Leveling Project is aimed to road updates and improvement of pavement quality. New Taipei City was selected as the subject for this study. International roughness index (IRI) was selected for field survey and statistical comparison. The outcome indicated that the IRI spread between 3.5 and 6.5 m/km before road leveling with an average of 4.71 m/km; the index fell between 2.5 and 4.5 m/km after road leveling with an average of 3.12m/km, suggesting that the IRI of the tested road sections showed a declining trend. For multi-lane road sections tested, the improvement was greater on the outer lanes than on the inner lanes. This proves that the implementation of the Road Leveling Project has made significant improvement in terms of pavement flatness. Suggestions are proposed in this study for the subsequent management and improvement polices of the Road Leveling Project, hoping that the pavement quality improvement continues to contribute to the extension of road service life and ride comfort.